2002
DOI: 10.1038/nm0202-166
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-secreting CD4+ T cells are crucial to the development of CD8+ T-cell responses against malaria liver stages

Abstract: CD4+ T cells are crucial to the development of CD8+ T cell responses against hepatocytes infected with malaria parasites. In the absence of CD4+ T cells, CD8+ T cells initiate a seemingly normal differentiation and proliferation during the first few days after immunization. However, this response fails to develop further and is reduced by more than 90%, compared to that observed in the presence of CD4+ T cells. We report here that interleukin-4 (IL-4) secreted by CD4+ T cells is essential to the full developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
181
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(193 citation statements)
references
References 39 publications
7
181
2
3
Order By: Relevance
“…Most importantly, the helper/inducer activity of RTS,S-immune CD4 ϩ T cells was evident only in cultures containing RTS,S-immune, but not naive CD8 ϩ T cells. Despite the preliminary nature of these observations, there is growing evidence that expansion as well as responses of Plasmodia Ag-generated CD8 ϩ T cells depend upon support from CD4 ϩ T cells (34,35).…”
Section: Cd4 ϩ and Cd8 ϩ T Cells Produce Ifn-␥mentioning
confidence: 99%
“…Most importantly, the helper/inducer activity of RTS,S-immune CD4 ϩ T cells was evident only in cultures containing RTS,S-immune, but not naive CD8 ϩ T cells. Despite the preliminary nature of these observations, there is growing evidence that expansion as well as responses of Plasmodia Ag-generated CD8 ϩ T cells depend upon support from CD4 ϩ T cells (34,35).…”
Section: Cd4 ϩ and Cd8 ϩ T Cells Produce Ifn-␥mentioning
confidence: 99%
“…CD4 T cells were important for the development of CD8 T cells specific for both T. gondii and malaria parasites (Gazzinelli et al 1991, Parker et al 1991). In the case of malaria (P. yoelii), it was possible to elegantly demonstrate that IL-4 secreted by CD4 T cells was crucial for the maturation, but not for the initial proliferation of specific CD8 T cells (Carvalho et al 2002).…”
Section: Conditions Of In Vivo Priming and Expansion Of Protective CDmentioning
confidence: 99%
“…In addition, soluble signals may be involved in CD8 + T cell formation. It has been reported that IL-4-secreting CD4 + T cells are involved in the formation of memory CD8 + T cells and recent results revealed that IL-2 signals during the priming phase are necessary for the development of memory CD8 + T cells [13][14][15]. In addition, lymphocytic choriomeningitis virus (LCMV) immunization experiments with IL-2R-deficient T cells showed that induction and maintenance of specific T cells was independent of IL-2R signaling, whereas IL-2R signaling was crucial for the secondary expansion of memory CTL [16].…”
Section: Introductionmentioning
confidence: 99%